Draft Annual Plan 1990-91 Haryana State - Planning Commission (Planning Commission, 1990)
Ever since its emergence as an independent State on 1st November, 1966, Haryana has made tremendous progress in every field of development. It has earned the distinction of being a trend setter in agriculture, industry, electrification, link-roads, irrigation, tourism and transport. There has been a remarkable improvement in health, education and other social services. Thus the basic strategy of Planning in Haryana has been to accelerate growth, promote self-reliance and improve all-round efficiency and productivity and to improve the living standards of the people in general, weaker sections in particular and to re-orient the educational & vocational programmes towards more effective utilisation of human resources.
Planning Department, Government of Haryana